Doxorubicin induced cardiotoxicity is mediated by increased CerS2 expression and ceramide accumulation in vitro and in vivo. (14th October 2021) - Kretzschmar, T; Wu, J M F; Bekhite, M; Gruen, K; Bogoviku, J; Mueller, T; Graeler, M; Franz, M; Schulze, P C
Abstract: Background: Doxorubicin (Dox) is a chemotherapeutic drug with cardiotoxicity as a severe side effect. Interestingly, Dox increases the expression of ceramide synthase 2 (CerS2) and increases long- chain ceramide levels with proinflammatory effects. Aim: The purpose of our study was to identify the role of increased long- chain ceramides synthesized by CerS2 in Dox mediated cardiotoxicity in vitro and in vivo. Methods: We incubated HL-1 cells (murine cardiomyocytes) with 0.7 μM Dox for 24h. In parallel cells were pretreated with fumonisin B (100 μM, 4h, FuB) to reduce Dox effects. We generated CerS2 ko mice and treated them with Dox and also generated doxycycline- inducible CerS2 mice. Expression of genes and proteins were measured with immunofluorescence (IF), western blot (WB) or qPCR. Ceramide levels were determined with mass spectrometry. Cellular staining was assessed by confocal laser scanning microscopy. Mitochondrial viability and activity were detected using seahorse analyzer. Results: Protein expression measurement showed increased CerS2 level in vitro (2.4±0.32, p=0.03 for WB, 2.2±0.10, p<0.001 for IF). Coherently, very long chain ceramides were increased with the highest peak for C16:0 (1.9±0.04, p<0.001). FuB pretreatment reduced most ceramides to normal levels. Dox increased mRNA level of TNFα (6.0±0.48, p<0.001), IL-6 (4.6±0.37, p<0.001), IL-1β (46.2±0.59, p=0.05) and BNP (4.7±0.46, p=0.03). FuB reduced IL-1β (20.1±0.23, p=0.002) and BNP (2.3±0.05, p=0.01) expression. Dox reduced mitochondria fusion related genes MFN1 (0.7±0.18, p=0.02) and MFN2 (0.3±0.37, p=0.01) and increased mitochondria fission related genes Mff (1.5±0.22) and FIS1 (1.5±0.18). FuB returned Mff and FIS1 expression to normal levels. Mitochondrial ATP production was reduced with Dox (0.3±0.19, p<0.001) and was slightly improved with FuB (0.5±0.12, p<0.001). Dox led to increased cleaved Casp3/Casp3 ratio (64.9±0.61, p=0.04). In vivo CerS2 overexpression showed comparable results as well as increased fibrosis. Conclusion: Our data show that Dox mediated cardiotoxicity is in part mediated by CerS2 and ceramides. CerS2 could be a valuable drug target for treatment of chemotherapy- associated cardiomyopathies. FUNDunding Acknowledgement: Type of funding sources: None.